The power of a blockchain-based supply chain. (September 2019) - Azzi, Rita; Chamoun, Rima Kilany; Sokhn, Maria
Highlights: Adopting different technologies and techniques create a reliable tracking system. Blockchain makes the supply chain secure, transparent, authentic and trustworthy. Blockchain used as a transactional network, to run and verify a smart contract. Dual data storage architecture is required to avoid degrading blockchain performance. All deployed sensors must be authenticated and must sign data before transmission. Abstract: A supply chain is a system of organizations, people, activities, information and resources involved in moving a product or service from supplier to customer. It is designed to maintain the quality of sensitive goods during the whole shipment. Centralized supply chain management systems expose the supply chain to corruption, fraud, and tampering. Blockchain has emerged as a new distributed information technology; it represents a new approach in supply chain area, where visibility and transparency of product flows are the principal challenges. This paper describes how the blockchain can be integrated into the supply chain architecture to create a reliable, transparent, authentic and secure system. To reach this goal, we studied the benefits of introducing the blockchain to the supply chain and the challenges encountered in a blockchain-based supply chain management ecosystem. We combined theoretical and real-world application studies to build our theory about the requirements for an efficient blockchain-based supply chain.